Susceptibility to degradation by absorbed hydrogen of AISI 1045 steel subjected to tests of slow traction and static fatigue in a hydrogenated medium - Vásquez García, Optaciano (2019)
In this paper is evaluation of susceptibility to hydrogen degradation ofAl SI steel 1045. Susceptibility of AISI 1045 steel to hydrogen embrittlement has been made by mechanical tensile test a static fatigue in hydrogen generation environments. Test were carred out using round notched specimens subjected to axial tensile load in O, IN EI2SO4 solution with to 0,25 g/1 arsenite sodium using hydrogen cathodic charging technique at densities current various. Reduction in area, tensile strength and fracture delayed of time were chosen relative changes as measures of susceptibility to hydrogen embrittlement. Fracture modes of failed samples were examined with of microscope. Mechanical test in inert environmental (air) comparisons and mechanical test in hydrogen generating environment show that both steels are susceptibility to hydrogen embrittlement.Samples of esferoidized steel have lower lost of ductility and strength than base metal samples. These variations in mechanical properties display a direct bearing on the current density. Also, both steels undergo changes in the fracture mode from a ductile to a brittle morphology in base metal while esferoidized morphology steel changes from highly ductile to a mixture of brittle fracture with ductile zones. These variations change with permanence time of hydrogen generated environmental steel.